PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DALAM MENINGKATKAN KREATIFITAS SANTRI - sahlan sahlan (Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2020)
This study aims to determine the transformational leadership style in fostering the creativity of An-Nawawi Islamic Boarding School students Berjan Purworejo. Data collection was carried out using interview and observation methods. From the results of data analysis, it is concluded that the creativity of a leader is obtained from the experience and knowledge he has, but that can be obtained by imitating or learning from the experience gained. The subjects showed a transformational leadership style of fostering creativity by applying critical thinking and good moral standards, giving new tasks to build potential and providing training and direction so that the work can be completed on time and efficiently. What is unique about the subject is its ability to entrust all the responsibilities given to the unit to be able to complete its tasks in its own way and ideas but still according to work procedures.Keyword: Curriculum Development, Islamic Education, Deradicalization.